1998
DOI: 10.1136/pgmj.74.877.662
|View full text |Cite
|
Sign up to set email alerts
|

Does psychological intervention help chronic skin conditions?

Abstract: SummaryThe objective ofthe study was to assess the impact of psychological/psychiatric assessment in patients with chronic or intractable dermatological conditions. A diagnostic interview was undertaken in order to pin-point any temporal connection between an adverse life-event and the first appearance of the skin disorder. Following this, the dermatologist's assessment of subsequent changes in the skin disorder were noted. The three main dermatological diagnoses were atopic eczema (10), prurigo (10), and psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 3 publications
0
18
1
2
Order By: Relevance
“…The role of psychological stress might be of particular relevance in patients affected by chronic or intractable skin conditions, as suggested by a recent study in which 69% of 64 patients with a chronic or treatment-refractory dermatological condition reported that a significant life event occurred at or about the time of onset of the skin condition [115]. However, the problem is to assess whether stress-induced onset or exacerbation represents idiosyncratic reactions in a few particular individuals or rather a phenomenon that occurs in a substantial proportion of cases, though probably not in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of psychological stress might be of particular relevance in patients affected by chronic or intractable skin conditions, as suggested by a recent study in which 69% of 64 patients with a chronic or treatment-refractory dermatological condition reported that a significant life event occurred at or about the time of onset of the skin condition [115]. However, the problem is to assess whether stress-induced onset or exacerbation represents idiosyncratic reactions in a few particular individuals or rather a phenomenon that occurs in a substantial proportion of cases, though probably not in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The multidisciplinary approach, namely the collaboration of specialists form the fields of psychiatry and dermatology and co-leading of the diagnostic process and treatment is essential for patients with psychodermatological diseases [26]. Dermatologists emphasize the importance of collaborating with psychiatrists as psychological factors play a significant part in such difficult to treat, chronic diseases of the skin as eczema, psoriasis and neurodermatitis [27,28]. However, patients with skin diseases with factors of psychological background often refuse the proposal of a psychiatric consultation, even thought it was proven that the cooperation between primary care physician, dermatologists and psychiatrists is very useful and effective in the treatment of such disorders [29].…”
Section: Resultsmentioning
confidence: 99%
“…A study of 64 patients suffering from a chronic dermatological disease and who were resistant to a well-managed treatment shows the presence of stressful life events for 69% of them [15]. …”
Section: Discussionmentioning
confidence: 99%